High Sar (Sodium Adsorption Ratio) Irrigation and Boron Phytotoxicity in Sugarbeet - Mehrotra, N K; Khan, S A; Aggarwal, S C (Annals of Arid Zone, 2016)
A pot-culture study em boron toxicity to sugarbeet plants (Beta vulgaris L.) under irrigation with graded sodic water (SAR 0.5.20 and 40) was conducted. Plants of cv ’Ramonskaya’ were grown at three levels of applied boron (B), 1 ppm (normal), 10 ppm (phytotoxic) and 20 ppm, in a loamy-sand alluvial soil amended with N, p. K, Fe, Mn, Cu, Zn and Mo. visible effects of B toxicity developed in the plants at 0.5 SAR given excess B (10 and 20 ppm) at 15-week growth and the symptoms intensified with age. The boron phytotoxicity was associated with an increase in the available soil-B, leof-B and top/root ratio of tissue B and decrease in root and total plant yield and tissue ratios, more so in top than in root, of Na/B and Ca/B. The excess B effects were merkedly reduced at high (20 and 40) SAR. This was associated with a marked reduction in the high SAR-induced decreass in available soil B. wot and total plant yield, ratios of top/root of tissue Band Ca/B, both in top and root, at excess (20 ppm) as compared to normal (1 ppm) level of B application. Results indicate antagonistic relationship between levels of soil B application and SAR of irrigation waters.